Функціональний стан вазопресинергічної системи гіпоталамуса при багатоденній дії переривчастої гіпоксичної гіпоксії - Абрамов, Андрій Володимирович; Колесник, Юрій Михайлович; Шаменко, Вадим Олександрович; Abramov, A. V.; Kolesnik, Yu. M.; Shamenko, V. A. (My University, 2018)
Важливою ланкою активації гіпоталамо-гіпофізарно-адненокортікальної системи при адаптації організму до дії гострих і хронічних стресорів є вазопресинергічна система гіпоталамуса. Основна частина вазопресин-синтезуючих нейронів локалізується у супраоптичному ядрі (SON), а також у латеральної частині заднього крупноклітинного суб'ядра (PVHpml) та у медіальному дрібноклітинному суб'ядрі (PVHmp) паравентрикулярного ядра гіпоталамуса. Мета роботи - вивчити особливості синтезу і секреції вазопресину пептидер-гічними нейронами гіпоталамуса при багатоденної дії переривчастої гіпоксичної гіпоксії та у віддалений постгіпоксичний період. Матеріали та методи. Дослідження проведено на 24 самцях щурів лінії Wistаr. Переривчаста гіпоксія моделювалася щоденним 6-годинним перебуванням щурів на висоті 6000 м (р02 = 9,8%) протягом 15 днів, постгіпоксичний період тривав 10 днів. Розподіл [Arg8]-вазопресину (АVР) досліджували методами кількісної іму-нофлуоресценції у серійних фронтальних зрізах гіпоталамуса. Результати. Гіпоксичні тренування сприяли підвищенню площі імунореактивності до АVР в аксонах SON без зміни цього показника у самих нейронах. Але вміст АVР в нейронах SON знижувався у 2 рази, а в аксонах мав тенденцію до підвищення (р=0,0505). У постгіпоксичний період вміст АVР у нейронах SON відновлювався, а в аксонах залишався на 15% менше, ніж в контролі. У PVHpml гіпоксичні тренування приводили до зростання вмісту АVР у нейронах та їх аксонах у 6 разів. Дані показники частково знижувалися у постгіпоксичний період, але залишалися достовірно вище за показниками контролю. У PVHmp гіпоксичні тренування призводили до 2-кратного підвищення площі імунореактивності до АVР у нейронах та до 4-кратного підвищення цього показника в аксонах. Вміст АVР у нейронах збільшувався в 6разів, а в аксонах - у 8 разів. У постгіпоксичний період в PVHmp відбувалася значна депресія даних показників, площа імунореактивності до АУР в нейронах ставала в 9 разів менше, ніж в контролі, а вміст АVР-у 2 рази менше. Висновки. Гіпоксичні тренування призводять до різних змін функціонального стану АVP-ергічної системи гіпоталамуса: в PVHmp і в PVHpml відзначається підвищення синтезу і секреції АVР. У постгіпоксічний період в PVHmp спостерігається значне пригнічення синтезу і секреції АVР, а в PVHpml показники активності АVР-ергічної системи залишаються підвищеними. У SON дія гіпоксії супроводжується незначним пригніченням синтезу АVР, яке відновлюється в постгіпоксічний період. The vasopressinergic system of the hypothalamus is an important neuroendocrine element of activation of the hypothalamic-pituitary-adrenocortical system in organism adaptation to the action of acute and chronic stressors. Most of the vasopressin-synthesizing neurons are localized in the supraoptic nucleus (SON), as well as in the lateral part of posterior magnocellular subnucleus (PVHpml) and the medial parvocellular subnucleus (PVHmp) of the paraventricular nucleus of the hypothalamus. Objective. To study the features of synthesis and secretion of vasopressin with the hypothalamus peptidergic neurons under the influence of many days intermittent hypoxic hypoxia and in the remote post-hypoxic period. Material and methods. The research was carried out on 24 male Wistar rats. Intermittent hypoxia was modeled by daily 6 hour stay of rats at the simulated altitude of 6000 m (p02=9,8%) for 15 days, the post-hypoxic period lasted 10 days. The distribution of [Arg8]-vasopressin (AVP) was investigated by quantitative immunofluorescence methods in serial frontal sections of hypothalamus. Results. Hypoxic training sessions stimulated an increase of immunoreactivity area to AVP in SON axons without change of immunoreactivity area in neurons. In addition to that the AVP content decreased 2-fold in SON neurons, and manifested tendency to elevation (p=0.0505) in axons. In the post-hypoxic period, the AVP content was restored in SON neurons, while it was 15% less in axons as compared with the control group. Hypoxic training sessions resulted in a 6-fold elevation of the AVP content in neurons and their axons in PVHpml. These indicators partially decreased in the post-hypoxic period, but remained significantly higher in the control group. Hypoxic training sessions resulted in a 2-fold increase in immunoreactivity area to AVP in PVHmp neurons and a 4-fold increase in axons. The AVP contents in neurons increased 6-fold, and in axons 8-fold. In the post-hypoxic period there was a high depression of these indicators in PVHmp. In addition to that the immunoreactivity area to AVP in neurons became 9 times smaller as compared with the control group, and AVP content was 2 times less. Conclusions. Hypoxic training sessions lead to various changes in the functional state of the hypothalamus vasopressinergic system: increase of synthesis and secretion of AVP is marked in PVHmp and in PVHpml. In the post-hypoxic period a significant inhibition of the synthesis and secretion of AVP is observed and in PVHmpl indices of the activity of the AVP-ergic system remain to be increased. In SON, hypoxia action is accompanied with a minor inhibition of AVP synthesis, which is restored in the post-hypoxic period.
The functional status of vasopressinergic system of the [Arg8]- hypothalamus under the influence of prolonged intermittent vasopressin,hypoxic hypoxia
Keywords: [Arg8]-вазопресин; гіпоталамус; гіпоксична гіпоксія; [Arg8]-vasopressin; hypothalamus; intermittent hypoxic hypoxia